RETRACTED: The effect of solar radiation on solar panels located in the open and placed in the shade of a building - Kuchkarov Akmal; Muminov Shermuhammad; Frid Semen; Madaliev Murodil (BIO Web of Conferences, 2024)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001